Discrete dynamic equilibrium model for a complex problem of flutter interactions. (December 2020) - Ario, Ichiro
Highlights: In this study we model a complex fluid dynamics behaviour using the low-ordered simplified nonlinear discrete model. The current complex phenomena of the coupling iteration between fluid and solid mechanics has the high-order-terms or huge calculations, for example CFD. We examine changes the theoretical model and different equation from the discrete mechanics with bifurcation based on chaos theory and post-buckling theory. We obtain approximate results from both experimental data and present method in global view. We forecast this complex phenomena using global bifurcation diagram based on non-equilibrium discrete mechanics by this present model. Abstract: The dynamic bifurcation analysis of the nonlinear oscillation of a simple fluidelastic structure is presented. This structure is a cantilever beam in a flow, and it behaves as a nonlinear system without potential energy. The structure demonstrates complex flutter behaviour that varies with the controlled flow velocity. We observe the flutter behaviour in a flow experiment, and the motion is characterised with this present model based on chaos theory of discrete dynamics. We can readily find the solution of the simple system, with which it is possible to create a map of the complex flutter behaviour.